Identifikasi Trichomonas vaginalis pada Urin Pekerja Seks Komersial dengan Menggunakan Metode Mikroskopis di Kota Bitung: Identification of Trichomonas vaginalis in Urine of Commercial Sex Workers Using Microscopic Methods in Bitung City - Indra Elisabet Lalangpuling; Valda Gavrila Sahentombage; Sabrina Pinontoan (Media Publikasi Cendekia Indonesia, 2023)
Sexually transmitted infections are infections that are mostly transmitted through sexual intercourse, be it vaginal (through the vagina), anal (anus/rectum) or oral (by mouth) sex. Trichomonas vaginalis is a parasite that causes the most sexually transmitted diseases in the world. A sexually transmitted disease caused by Trichomonas vaginalis is Trichomoniasis. Commercial Sex Workers (PSK) whose job is to serve sexual activities with the aim of getting wages or money for their services is a route that plays a very important role in the transmission of various sexually transmitted diseases. This research was conducted to identify the protozoa Trichomonas vaginalis in the urine of commercial sex workers in Bitung City. This research is descriptive in nature, carried out by collecting primary data from observations and examinations in the laboratory. Purposive sampling and samples obtained as many as 30 samples from CSWs in Bitung city. Data from microscopic examination results can be presented in the form of tables or diagrams and narrated descriptively. Based on the results of the study, 9 positive samples were obtained with a presentation of 30% infected with Trichomonas vaginalis. The conclusion of this study is that Trichomonas vaginalis infection was found in commercial sex workers in Bitung